Understanding and Managing Social–Ecological Tipping Points in Primary Industries. (8th May 2019) - Yletyinen, Johanna; Brown, Philip; Pech, Roger; Hodges, Dave; Hulme, Philip E; Malcolm, Thomas F; Maseyk, Fleur J F; Peltzer, Duane A; Perry, George L W; Richardson, Sarah J; Smaill, Simeon J; Stanley, Margaret C; et al.
Abstract: Global environmental change and humanity's growing demands for resources have generated concerns regarding how much pressure Earth systems can absorb without drastic, potentially irreversible consequences. In natural resource production systems, tipping points can generate immediate threats to human well-being. However, empirically exploiting conceptual tipping point models, and applying that learning to management has proven challenging. We argue that primary industries are characterized by a set of social and ecological features that predisposes them to tipping points and motivates studying them as a special class of social–ecological systems. Several primary industry features and feedback loops can explain why some resource systems face a high risk of tipping points, how social responses can affect the detection of early warnings, and how tipping points may cascade among primary industry subsystems. New understanding of resource resilience could be gained by complementing current research with a primary industry perspective. We discuss challenges and solutions for this research agenda.